Fellows perspective of HPB training in Latin America. Issue 1 (January 2020) - Domínguez-Rosado, Ismael; Espinoza, Johana L.; Alvarez, Fernando A.; Vintimilla, Agustin; Quintero, Marco; Barzallo, David; Pekolj, Juan; Gondolesi, Gabriel; Schelotto, Pablo B.; Herman, Paulo; Carneiro D'Albuquerque, Luiz A.; Andraus, Wellington; et al.
Abstract: Background: Currently, no standards for HPB training exist in Latin America. The aim of this work is to evaluate fellows' experience of HPB training and the areas of opportunity to improve. Methods: A 35 points survey was developed and distributed among fellows from dedicated HPB training programs in Latin America. The survey was applied by direct phone call (37%) or web based (63%), to fellows graduated between 2010 and 2014, from 7 different programs. Results: Thirty-nine fellows from Argentina, Brazil, Chile and México were considered with a response rate of 82% (32/39). Most fellows (90%) shared cases with more than one co-fellow. Scrubbing with chief residents ocurred to 60% of fellows; only 14% of fellows noted having a primary surgeon role in more than 70% of cases. Median number of major hepatectomies during training was 15 (1–100), Whipple procedures 6 (1–40), and major bile duct repair 20 (1–80). Limited funding was the main reason to avoid HPB programs outside the country of origin. Conclusion: HPB training in Latin America requires more operative volume and autonomy. Financial burden is the main limitation to pursue training overseas. A multinational fellowship that takes advantage of each center may overcome differences in volume and type of cases.